2021
DOI: 10.1590/1678-4324-2021210327
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Lavandula dentata L. Essential Oil on Anticarsia gemmatalis (Hübner, 1818)

Abstract: Anticarsia gemmatalis, commonly known as soybean caterpillar, causes important economic losses in soybean crops. Synthetic pesticides are the standard practice to control this insect. However, the indiscriminate use of these substances has increased the resistance of this pest. Thus, it is necessary to search for different control alternatives that are also more environmentally friendly. The objective of this work was to evaluate the chemical composition of Lavandula dentata L. essential oil (EO) and its activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…For example, the insecticidal activity evaluation of some aromatic plants, including L. dentata showed that L. dentata EO at the concentration of 0.6% v/v resulted in 100% mortality after 24 h of exposure to Anticarsia gemmatalis. 30 Wagner et al (2021) 31 reported a significant fumigant potential of Lavandula dentata EO against adults of Sitophilus zeamais, Tribolium castaneum and Epicauta atomaria. In the same vain, a potent toxic effect has been reported for L. angustifolia EO against Acanthoscelides obtectus (100% mortality at 2 and 80 μL/L of air).…”
Section: Insecticidal Activity Of Lavandula Dentata Essential Oilmentioning
confidence: 99%
“…For example, the insecticidal activity evaluation of some aromatic plants, including L. dentata showed that L. dentata EO at the concentration of 0.6% v/v resulted in 100% mortality after 24 h of exposure to Anticarsia gemmatalis. 30 Wagner et al (2021) 31 reported a significant fumigant potential of Lavandula dentata EO against adults of Sitophilus zeamais, Tribolium castaneum and Epicauta atomaria. In the same vain, a potent toxic effect has been reported for L. angustifolia EO against Acanthoscelides obtectus (100% mortality at 2 and 80 μL/L of air).…”
Section: Insecticidal Activity Of Lavandula Dentata Essential Oilmentioning
confidence: 99%